Force Majeure and the Duty of Spousal Maintenance: A Sociological Jurisprudence Study of Semeru Eruption Survivors in Lumajang - Fadia Imtila'ul Amalia; Muhammad Aminuddin Shofi; Habeb Sufyan Mohamed Redhwan (Fenomena, 2026)
The recurring eruptions of Mount Semeru have created a critical disjuncture between Islamic law's normative requirement that husbands provide spousal maintenance (nafkah) and the socioeconomic realities faced by disaster-affected families, yet limited research has examined this intersection through a sociological jurisprudence lens. This study analyzes the implementation of husbands' maintenance obligations under force majeure conditions among Semeru eruption survivors in Supiturang Village, Lumajang Regency. Using majeure-affected juridical-sociological methodology, data were collected through in-depth interviews, observations, and documentation from seven informants—including husbands, wives, and community leaders—and analyzed descriptively and analytically using triangulation. The findings reveal that, while the normative obligation remains legally binding, its implementation is adjusted to actual economic capacity through economic adaptation strategies, wives' participation in productive activities, and community social support. From a sociological jurisprudence perspective, law operates adaptively and contextually in responding to the social dynamics of disaster-affected communities, with nafkah implementation interpreted not formally but in accordance with principles of justice, benefit, and capability. These findings underscore the necessity for responsive legal policies and community-based family economic assistance programs tailored to the socioeconomic vulnerabilities of force majeure-affected communities. Erupsi berulang Gunung Semeru telah menciptakan kesenjangan kritis antara kewajiban normatif hukum Islam bagi suami untuk memberikan nafkah dan realitas sosial-ekonomi yang dihadapi keluarga terdampak bencana, namun penelitian yang mengkaji persimpangan ini melalui perspektif sociological jurisprudence masih terbatas. Penelitian ini menganalisis pelaksanaan kewajiban nafkah suami dalam kondisi force majeure pada masyarakat penyintas erupsi Semeru di Desa Supiturang, Kabupaten Lumajang. Menggunakan metodologi kualitatif yuridis-sosiologis, data dikumpulkan melalui wawancara mendalam, observasi, dan dokumentasi dari tujuh informan—terdiri dari suami, istri, dan tokoh masyarakat—serta dianalisis secara deskriptif-analitis dengan menggunakan teknik triangulasi. Temuan menunjukkan bahwa meskipun kewajiban normatif tetap mengikat secara hukum, implementasinya mengalami penyesuaian kontekstual berdasarkan kemampuan ekonomi aktual melalui strategi adaptasi ekonomi, partisipasi istri dalam aktivitas produktif, serta dukungan sosial dari masyarakat. Dari perspektif sociological jurisprudence, hukum bekerja secara adaptif dan kontekstual dalam merespons dinamika sosial masyarakat terdampak bencana, dengan implementasi nafkah yang tidak dimaknai secara formalistik, melainkan berdasarkan prinsip keadilan, kemaslahatan, dan kemampuan. Temuan ini menegaskan perlunya kebijakan hukum responsif dan program bantuan ekonomi keluarga berbasis komunitas yang disesuaikan dengan kerentanan sosial-ekonomi masyarakat terdampak force majeure.